2020
DOI: 10.1007/s10530-020-02297-3
|View full text |Cite
|
Sign up to set email alerts
|

Breeding consequences for a songbird nesting in Argentine ant’ invaded land

Abstract: The consequences of ant invasions on ecosystems may only become apparent after long periods. In addition, predicting how sensitive native fauna will respond is only possible if the underlying proximate mechanisms of their impact are identified. We studied the attraction of the native and invasive ant community to artificial bird nests. Further, we studied reproduction of a wild native songbird over five consecutive breeding seasons in relation to the presence of an invasive ant species. We analysed biometric, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Although L. humile is generally linked to loss of native arthropod populations in Coastal Sage Scrub habitat [75][76][77], within the territories we studied-all of which were invaded-we did not detect an association between variance in L. humile and prey abundance or composition. While L. humile can attack and harass nestlings [46] and has otherwise been observed to affect bird performance [78], the effect on date of first egg laying-our performance metric-cannot be explained by such dynamics unless adults perceived higher L. humile densities as being indicative of poor habitat quality and delayed egg laying. There was a strong positive association between L. humile and A. vulgare on the ground, and it is thus possible that some component of the negative effect of L. humile was mediated by their facilitating A. vulgare.…”
Section: Plos Onementioning
confidence: 99%
“…Although L. humile is generally linked to loss of native arthropod populations in Coastal Sage Scrub habitat [75][76][77], within the territories we studied-all of which were invaded-we did not detect an association between variance in L. humile and prey abundance or composition. While L. humile can attack and harass nestlings [46] and has otherwise been observed to affect bird performance [78], the effect on date of first egg laying-our performance metric-cannot be explained by such dynamics unless adults perceived higher L. humile densities as being indicative of poor habitat quality and delayed egg laying. There was a strong positive association between L. humile and A. vulgare on the ground, and it is thus possible that some component of the negative effect of L. humile was mediated by their facilitating A. vulgare.…”
Section: Plos Onementioning
confidence: 99%
“…There is ample literature documenting antagonistic ant‐bird interactions, primarily in the form of bird predation on ants (reviewed in Avilés, 2024 ). There are also studies reporting negative effects of ants on aspects such as bird abundance, behaviour and reproduction, primarily through predation on eggs and chicks (Álvarez‐Blanco et al., 2020 ; Davis et al., 2008 ; Haemig., 1999 ). However, assessing the impact of ants on more mobile segments of a population (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ants and birds are enormously abundant and species-rich taxa in the same communities [ 6 ], and therefore likely to encounter each other or share key resources. Indeed, some studies have shown that both birds and ants can act as predators in bird–ant interactions [ 7 , 8 ]. In addition, empirical work has reported a maintenance ‘anting behaviour’ during which birds rub ants on their feathers and skin [ 9 ].…”
Section: Introductionmentioning
confidence: 99%